1997
DOI: 10.1046/j.1464-410x.1997.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence of decreased contralateral testicular blood flow during ipsilateral testicular torsion

Abstract: Objective To evaluate contralateral testicular blood flow eral testes of the torsion group were collapsed. The diÂerence between the contralateral testes of the two by histological examination of arterioles during ipsilateral testicular torsion.groups and between the ipsilateral and contralateral testes in the torsion group were significant. The diamMaterials and methods The study comprised two groups of 20 male albino rats (weight 250-270 g). The eter of uncollapsed arterioles did not diÂer significantly amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Several mechanisms, including an immunological phenomenon, release of acrosomal enzymes, blood flow alterations, an underlying congenital testicular defect, presence of underlying defect of spermatogenesis, paired neuroendocrine or vasomotor response during torsion and subclinical attacks of contralateral testicular torsion, are claimed to be responsible on this issue. 2,4,[20][21][22][23][24][25] In the testicular tissue, MTBS is used to assess histopathological damage. It is based on the evaluation of progressive degeneration of the germinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms, including an immunological phenomenon, release of acrosomal enzymes, blood flow alterations, an underlying congenital testicular defect, presence of underlying defect of spermatogenesis, paired neuroendocrine or vasomotor response during torsion and subclinical attacks of contralateral testicular torsion, are claimed to be responsible on this issue. 2,4,[20][21][22][23][24][25] In the testicular tissue, MTBS is used to assess histopathological damage. It is based on the evaluation of progressive degeneration of the germinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several recent clinical and experimental studies of contralateral testicular injury after UTT; most of these studies [1±12] reported contralateral testicular damage, with speci®c histological [1,3,9±11] and biochemical [5] changes after UTT, although others disagree [13±17]. Of the several proposed causes for such damage, a re¯ex decrease in contralateral testicular blood¯ow is probably the most likely [2,5, 12,18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that ipsilateral testicular torsion may cause oxidative stress and injury in the contralateral testicle. Several mechanisms, such as an increase in biomarkers that cause DNA changes (21), apoptosis (22), free oxygen radical secretion from the testicle (23), refl ex decrease in contralateral testicle blood fl ow (24), and autoimmunization by the destroyed blood-testicle barrier (25), have been described. However, other studies were unable to show injury in the contralateral testicle (26,27).…”
Section: Discussionmentioning
confidence: 99%